Strobilanthes medahinnensis (Acanthaceae) a new species, based on morphological and molecular data, from the Peak Wilderness Nature Reserve, Sri Lanka - Nilanthi, Rajapakse Mudiyanselage Renuka; Samarakoon, Hiruna; Jayawardana, Nuwan; Wijesundara, Siril; Bandaranayake, Pradeepa Chandani Gunathilake (Phytotaxa, 2021)
Strobilanthes medahinnensis, a new species of Acanthaceae is described and illustrated from Sri Lanka. The new species is similar to S. anceps in having ovate leaves, yellow gland dots of abaxial leaf surface and reflexed bracts but differs by rounded stem, leaves with acuminate apex, elongated spikes, lanceolate outermost bract with long acuminate apex. The establishment of the new species is supported by complete plastome genome analyses.